KARYOTYPE STUDIES IN 22 SPECIES OF PARROTS (PSITTACIFORMES, AVES) - Delucca, E. J.; Shirley, L. R.; Lanier, C. (Soc Brasil Genetica, 1991)
The karyotypes of 12 species of Psittaciformes new to cytology are described: Lorius hypoinochrous, L. lory and Phigys solitarius of the Loriidae, and Amazona autumnallis, Aratinga jandaya, Eclectus roratus, Pionus maximiliani, P. menstruus, P. senilis, P. seniloides, Poicephalus senegalus and Polytelis alexandrae of the Psittacidae. The karyotypes of Amazona ochrocephala, Ara ararauna, Ara macao, Psittacula krameri, Psittacus erithacus and Pyrrhura molinae of the Psittacidae have been previously described. For reasons of comparison the karyotypes of Aratinga aurea, Forpus xanthopterygius, Brotogeris sanctithomae and B. versicolorus of the Psittacidae are also described. These karyotypes are compared to those in the literature and the karyological relationships in the Psittaciformes are briefly discussed. Microchromosome fusions and translocations and pericentric inversions probably are responsible for the heterogeneity of karyotypes in the Psittaciformes.